1997
DOI: 10.1089/vim.1997.10.21
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Herpesvirus 1 Downregulates the Expression of Bovine MHC Class I Molecules

Abstract: The mechanism of immunosuppression induced by bovine herpesvirus 1 (BHV-1) was investigated by studying the effects of the virus on the expression of major histocompatibility complex (MHC) class I molecules. After infection with the virus, the expression of class I molecules was detected by flow cytometry and pulse-chase analysis. A selective downregulation of expression of class I molecules was seen in the infected cells, while the class II expression remained unaffected. The reduction in surface expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…In order to diminish the detection and the elimination of virus-infected cells by cytotoxic T lymphocytes, BoHV-1 was shown to down-regulate antigen presentation by the class I major histocompatibility complex (MHC class I) [95,96,115,146]. Two independent mechanisms are responsible for down-regulation of MHC class I molecules.…”
Section: Immune Response and Immune Evasion Strategiesmentioning
confidence: 99%
“…In order to diminish the detection and the elimination of virus-infected cells by cytotoxic T lymphocytes, BoHV-1 was shown to down-regulate antigen presentation by the class I major histocompatibility complex (MHC class I) [95,96,115,146]. Two independent mechanisms are responsible for down-regulation of MHC class I molecules.…”
Section: Immune Response and Immune Evasion Strategiesmentioning
confidence: 99%
“…MHC class I molecules are composed of a single membrane-spanning heavy chain (including α1, α2 and α3 domains) paired with the soluble protein β2 microglobulin (β2m), which construct a groove in their membrane distal domain (α1α2 or α1β2) that binds peptides in order to display them to the T cells of the cellular immune response [45]. MHC-I heavy chain RNA could be downregulated by bovine papillomavirus E5 oncoproteins and bovine herpes virus [46,47]. A bovine B cell line infected by bovine leukemia virus (BL3.1) is distinguished by a loss of expression of surface MHC-I, which correlates with a diminution in MHC-I heavy chain transcription due to loss of a transactivator [48].…”
Section: Classical Mhc-i Transcription In Pbmcs Of Pregnant Cows and mentioning
confidence: 99%
“…The latter is known to decrease host defence amongst others by diminishing the activities of T lymphocytes, B lymphocytes, monocytes and macrophages [24,67] and by interfering with the host's antigen presentation machinery to evade the host's immune response in vivo [74,134]. Moreover, it has been shown that leukocyte exposure to inflammatory cytokines released in response to BHV-1 infection (interleukin-1 beta, interleukin-8, tumour necrosis factor alpha and interferon gamma) can modulate the migration and functional activation of bovine leukocytes [26,105,106].…”
Section: Molecular Synergies With Other Pathogensmentioning
confidence: 99%